2021
DOI: 10.1002/ajh.26379
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor T‐cells, bispecific antibodies, and antibody‐drug conjugates for multiple myeloma: An update

Abstract: Patients with multiple myeloma who are refractory to currently available effective therapies have short expected survival. Modalities harvesting the knowledge of the immune characteristics and microenvironment of myeloma such as chimeric antigen receptor (CAR) T-lymphocytes, bispecific antibodies (bsAbs), and antibody-drug conjugates (ADCs) have shown potential in early phase trials. Based on data from phase 2 studies, idecabtagene vicleucel (ide cel), an anti-B-cell maturation antigen CAR T-product and belant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 128 publications
0
21
0
1
Order By: Relevance
“…170 Several bispecific antibodies targeting various antigens on the myeloma cell surface have been tested in clinical trials, and have shown promising single-agent activity. 171 Bispecific antibodies have dual specificities to enable them to bind to both plasma cells and T cells. Most bispecifics (teclistamab, elranatamab, TNB-383B, AMG-701, REGN 5458) currently target the BCMA antigen on plasma cells and CD3 on T cells.…”
Section: Emerging Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…170 Several bispecific antibodies targeting various antigens on the myeloma cell surface have been tested in clinical trials, and have shown promising single-agent activity. 171 Bispecific antibodies have dual specificities to enable them to bind to both plasma cells and T cells. Most bispecifics (teclistamab, elranatamab, TNB-383B, AMG-701, REGN 5458) currently target the BCMA antigen on plasma cells and CD3 on T cells.…”
Section: Emerging Optionsmentioning
confidence: 99%
“…Of these, the most promising involves the use of bispecific antibodies 170 . Several bispecific antibodies targeting various antigens on the myeloma cell surface have been tested in clinical trials, and have shown promising single‐agent activity 171 . Bispecific antibodies have dual specificities to enable them to bind to both plasma cells and T cells.…”
Section: Treatment Of Relapsed Multiple Myelomamentioning
confidence: 99%
“…These results support the use of PSGL-1-targeted liposomal BTZ-containing formulations to overcome drug resistance and improve patient outcomes in MM ( 319 ). Several recent review papers summarize the plethora of available immunotherapies and their mechanism of action in MM (checkpoint inhibitors, or T-cell engaging bispecific antibodies and/or adoptive T-cell/NK cell therapy) ( 320 322 ), therefore we will not cover this topic in the present review. Targeting the interaction of malignant PCs with the TME may weaken the TME-mediated drug resistance and/or decrease the immunosuppressive activity and environment induced by active MM.…”
Section: Overcoming Tme-mediated Pi Resistancementioning
confidence: 99%
“…The continued expression of BCMA in some patients relapsing on BCMA-based therapies provides the option of continuing to target this antigen. Agents include antibody-drug conjugates (ADCs), autologous chimeric antigen receptor engineered T cells (CAR-T), and bispecific T cell engagers [53,54].…”
Section: Promising Investigational Options Other Bcma-targeted Therapiesmentioning
confidence: 99%